Mycosis Fungoides: A Diagnostic Challenge - Siddhartha Nath; Arunima Dhabal; Indrashis Podder (University Library System, University of Pittsburgh, 2022)
Background: Mycosis fungoides (MF) is the most frequent type of cutaneous T-cell lymphomas (CTCL), a heterogeneous group of non-Hodgkin lymphoma of T-cell origin. CTCLs accounts for about 4% of all non-Hodgkin lymphoma. MF mainly involves the skin but in advanced cases it may involve the lymph, blood and other organs. It mimics other skin disorders like erythema necroticans, leprosy, psoriasis etc which leads to delayed diagnosis and subsequent treatment. Case report: A 61 year old male patient visited the OPD of a tertiary care hospital in Eastern India with multiple reddish elevated lesions for last 6 months which later became dome shaped and then ulcerated. He did not have any fever or itching. He informed that he had been taking Homeopathic medicine previously, but the identity of the said medicine could not be confirmed. Physical examination ruled out the presence of pallor, jaundice, oedema and cyanosis. Pulse and BP were within normal range. Systemic examination was unremarkable except mild hepatomegaly. Cutaneous examination revealed multiple erythematous indurated plaques, papules and nodules over chest, abdomen, back, limbs and face. Few of the plaques present on the trunk and left arm had developed ulcers having a necrotic floors. Cervical, axillary and inguinal lymph nodes were palpable, being firm in consistency and mobile in nature. Hair, nail and mucosal examination revealed normal results. Complete blood count (CBC), peripheral blood smear(PBS), serum urea and creatinine level did not deviate from normal findings. Ultrasonography of whole abdomen showed a mildly enlarged liver. A prominent lymph node in the aortocaval groove could be appreciated on the computed tomography(CT) scan of  whole abdomen. CT scan of chest revealed bilateral axillary lymphadenopathy. Erythema necroticans, sarcoidosis and CTCL were considered as the differential diagnoses. Lesional biopsy revealed irregular epidermal hyperplasia, parakeratosis and epidermotropism in the absence of spongiosis.There was infiltration of atypical lymphocytes in the epidermis, forming well developed Pautrier's micro abscesses. The lymphocytes were tagging the dermo-epidermal junction and within the epidermis showing surrounding halo, convoluted nuclei and variable nuclear pleomorphism. Band like papillary dermal lymphoid infiltrate, dermal lymphoid fibroplasia and nodular lymphoid aggregates could be appreciated in the deep dermis. Immunohistochemical tests were performed and the immunophenotypic profile revealed positivity for CD2, CD3, CD5, CD7, CD 8 and TIA1 and negative for CD4, CD20, CD30, CD56 and granzyme B. Based on clinical presentation, histopathology and Immunohistochemical tests, a final diagnosis of MF was made. The patient was then started on systemic antibiotic therapy, due to increased risk of bacterial super infection of lesions due to skin barrier disruption. He was then referred to Oncology department for further treatment. Conclusion: In this case, the male patient was suffering from mycosis fungoides. In the background of its clinical features being similar to other skin disorders like erythema necroticans, clinicians may face a diagnostic dilemma to correctly diagnose it. Timely diagnosis and treatment improves the prognosis in most cases. Histopathological evaluation still remains the investigation of choice.